The influence of ROE, company size, DER, and EPS on stock price in mining sub-sector companies coal listed on BEI period 2018–2022 - Martia Ningsih; Gustia Harini; Erita Erita (Review of Management, Accounting, and Business Studies, 2022)
This research aims to analyze: 1) The return on equity on the company's stock price, 2) Company size to stock price, 3) Debt to Equity Ratio to stock price, 4) Earnings per share-to-stock price, 5) The return on equity, company size, Debt to Equity Ratio, and earnings per share against stock price. The type of research used is quantitative. The population of this research is all companies in the coal sub-sector listed on the Indonesia Stock Exchange, namely 24 companies with 5 research years (2018-2022). The sampling technique used the Purposive Sampling method with a total research sample of 19 companies. The data analysis technique uses the Ordinary Last Squares (OLS) method using the EViews program. The results of this research indicate that: First, there is no significant influence between Return on Equity (ROE) and stock prices. Second, company size has a significant impact on stock prices. Third, Debt to Equity has no effect on stock prices. The four earnings per share do not have a significant effect on stock prices.